(untitled) - Ghavami, M. (Chichester, UK, 2007)
The book explains the basic signal processing that underlies current ultra-wideband systems, in order to provide a foundation that will remain useful as applications and regulations change. The content focuses on civilian communications applications
Keywords: Broadband communication systems,Ultra-wideband devices,Hệ thống truyền thông băng thông rộng,Thiết bị siêu cao tần